Cardiac care for Indigenous Australians: practical considerations from a clinical perspective. Issue 1 (3rd July 2017) - Walsh, Warren F; Kangaharan, Nadarajah
Summary:   Indigenous Australians have a much high burden of cardiovascular disease, which occurs at an earlier age than in the non‐Indigenous population. Comorbidities such as diabetes are common. Early diagnosis of ischaemic heart disease may be difficult because of barriers such as distance to medical centres, communication problems and family and cultural responsibilities. Disparities in cardiac care between Indigenous and non‐Indigenous populations are well documented, with examples including reduced angiography and revascularisation rates in Indigenous patients. Indigenous patients can have poor health literacy and need careful explanation of procedures, with the assistance of Aboriginal health workers, visual aids and family members. Acute rheumatic fever and chronic rheumatic heart disease remain ongoing health problems in Indigenous communities, especially in remote areas. Ambulatory care of Indigenous Australians with chronic cardiovascular disease is challenging. It requires well supported health care systems, including Aboriginal health workers and cardiac nurse coordinators to case‐manage patients. A holistic approach to care, with attention directed towards both cardiac and non‐cardiac comorbidities, is crucial for optimal management of cardiovascular disease in Indigenous Australians. Multidisciplinary care, involving an empowered and supported primary care team working together with specialists through outreach services or telehealth, is important for patients who are at high clinical risk and those living in remote areas. Indigenous Australians deserve the same level of evidence‐based cardiovascular health care and access to care as non‐Indigenous Australians.